Forecasting developments of the Car fleet in the Altrans model - Kveiborg, Ole (Proceedings from the Annual Transport Conference at Aalborg University, 1999)
The paper presents a submodel to the model complex ALTRANS (ALternative TRANSport systems). The model is thoroughly described in Kveiborg (1999). The Altrans model is a model developed for analysing the transport consequences of different policy proposals. The model is based on the transport behaviour of individuals in Denmark, and give among other things estimates of traffic performance by mode, and car ownership. The model presented here uses this information to calculate the energy consumption and the emissions stemming from the transport in cars. The paper includes a brief presentation of the overall model complex, and a slightly more thorough analysis of the historical development of the Danish car fleet. This development forms the basis for the model development. The general idea of the model and estimation results are discussed. Generally speaking the development in the car fleet is composed of three parts: the existing fleet, the purchase of new cars and the scrappage of old cars. The development is split into different groups of vehicles based on the age, weight and the type of fuel usage of the cars. Different exogenous variables are used in explaining the developments in both purchase and scrappage rates. Splitting the developments into these different groups makes it possible to calculate the energy consumption more accurately.